Reconocimiento de olor feromonal con específico en Waglerophis Merremii (Serpentes: colubridae) : Influencia estacional y hormonal - Chiaraviglio de Torres, Margarita (1994)
Tongue flicking responses of adult male and female Waglerophis merremii were tested with cloacal glands chemical stimuli of male and female conspecifics and control substance, ah l presented on cotton-tipped applicators. Tongue flicking rates by both sexes were significantly higher from cloacal chemical stimuli than from control, indicating that W. merremii detected conspecific cloacal chemicals. Postreproductive males treated with testosterone ernitted significantly more tongue-flicks in response to female than to male cloacal chemicals. Postreproductive females treated with estradiol emitted significantly more tongue -flicks in response to male than to female cloacal chemicals. Both results showed that W. merremii can chemically discriminate sex, suggesting the importance of pheromonal communication.